Directing the Diffusion of Public Opinions in Incidents with Not-in-My-Back-Yard Projects: An Evolutionary Perspective. (28th December 2022) - Liu, Xiaofeng; Wu, Xiaoling; Qiu, Yumin; Cheng, Shuping
Abstract : How should the public administrative department direct the diffusion of public opinions in a not-in-my-backyard (NIMBY) crisis? This paper first analyzes the macroevolutionary characteristics of the public opinion associated with a NIMBY crisis. We then examine the perceptive interactions among individuals towards NIMBY projects from a microscopic perspective and develop an evolutionary game model (i.e., replicator dynamics) to describe the interactions among individuals. We also use information entropy and dynamic equations to construct an interaction entropy model and a dynamic equation to capture administrative-department-led public opinion. Through examining the existence and stability of the evolutionary equilibrium of these models, we analyze the evolution of NIMBY public opinion.